1999
DOI: 10.1080/030919099294393
|View full text |Cite
|
Sign up to set email alerts
|

Blood damage, platelet and clotting activation during application of radiofrequency or cryoablation catheters: a comparative in vitro study

Abstract: During catheter ablation of cardiac tissue, the insulting stimulus may damage and activate the blood. Specifically activation of platelets and the clotting system is a potential risk by their formation of thrombi. In this study the effect of two different techniques, a radiofrequency and a cryo-application procedure, on the activation of platelets and clotting in an in vitro blood circulation model was investigated. The radio-frequency procedure induced significantly more blood cell damage, platelet activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 15 publications
(1 reference statement)
2
26
0
3
Order By: Relevance
“…The nature of emboli recorded during energy application (66% of the total number of cerebral MESs), and manipulation between the applications in the ENDO PVI (26% of the total cerebral MESs), are not completely understood. Both thrombi [15,18] as gaseous formation [16,17] could occur in both phases. Lickfett et al [6] demonstrated with diffusionweighted (DW)-MRI that 10% of the patients treated by a percutaneous endocardial ablation method had cerebral embolic lesions post-procedurally.…”
Section: Clinical Relevancementioning
confidence: 97%
See 1 more Smart Citation
“…The nature of emboli recorded during energy application (66% of the total number of cerebral MESs), and manipulation between the applications in the ENDO PVI (26% of the total cerebral MESs), are not completely understood. Both thrombi [15,18] as gaseous formation [16,17] could occur in both phases. Lickfett et al [6] demonstrated with diffusionweighted (DW)-MRI that 10% of the patients treated by a percutaneous endocardial ablation method had cerebral embolic lesions post-procedurally.…”
Section: Clinical Relevancementioning
confidence: 97%
“…In this study, 332 (AE193) cerebral MES were detected prior to the first energy application, which represents 8% of all the MES detected during the whole ENDO procedure, as shown in Table 2. When applying ablation energy on the endocardial wall of the ostia of the PV, the cardiac endothelium is damaged; this may lead to platelet adhesion and activation, thus resulting in clot formation [15]. Another cause of emboli during the applications could be linked to high temperatures.…”
Section: Causes Of Embolimentioning
confidence: 99%
“…An in vitro study demonstrated significant damage to blood cells and platelets with RFCA compared with catheter cryoablation. 550 A comparison of catheter cryoablation with RFCA in 30 adult patients has been reported by Tse et al 551 They found a significant increase in platelet activation in the RFCA group compared with the catheter cryoablation group. Several thrombotic parameters were elevated in both the catheter cryoablation and RFCA groups, observed immediately after sheath insertion.…”
Section: Catheter Cryoablationmentioning
confidence: 99%
“…Because the number of thromboembolic complications of RFA is low, identification of the risk factors is difficult and the significance of the pathophysiological mechanisms of hemostasis activation during RFA has not been definitively established in studies published to date. T0 before insertion of sheaths, T1 end of EPS, T2 30 min after completion of RFA, DD D-dimers, TAT thrombin-antithrombin III, PAI-1 plasminogen activator inhibitor type 1, t-PA tissue-type plasminogen activator, CPAi circulating platelet aggregates index, LCL lower confidence level, UCL upper confidence level Potential mechanisms of thrombogenesis during ablation procedures are multiple and include endothelial disruption, coagulation necrosis, electroporation injury, mechanical damage of the vessel wall, and heating of circulating blood elements by RF energy [9][10][11][12][13][14][15][16][17][18]. Sasano et al [19] concluded that the thrombogenesis caused by RFA has 2 phases; in the acute phase hemostasis activation occurs during placement of the catheters and in the delayed phase thrombogenesis is the result of endothelial damage caused by the RF current.…”
Section: Discussionmentioning
confidence: 99%